Classes, strates sociales et émergence de la " Petite paysannerie " à Saint-Domingue-Haïti (1640-1835) - Samedy, Jean-Baptiste Mario (Anthropologica, 2022)
On the Saint-Domingue-Haiti social formation, there is a current theory explaining the Saint-Domingue Revolution as stemming from the Bourgeois French Revolution while insisting that the lower pesantry was not born until the end of 1805. This article wants to show that the Saint-Domingue Revolution is the result of the praxis of the struggles and alliances between certain indigenous classes and social Stratas. These struggles and alliances were supported by the intercolonial war between France, England, and Spain. In this picture, the lower peasantry appeared before 1805 in the complex network of colonialist esclavagist social relations of production of Saint-Domingue and continues to exist afterwards bringing about, with intensity, the problem of the Haitian Agrarian Revolution.